SOCIAL AND LABOUR ADAPTATION OF YOUTH IN THE CONDITIONS OF WORLD ECONOMIC CRISIS - Cherevko, O. V.; Snachov, M. P. (Science and Transport Progress, 2009)
In this article the principal causes of youth unemployment on a labor market are investigated and some recommendations concerning the solution of this problem, which realization can improve social-and-labor adaptation of the youth in conditions of the world economic crisis, are offered.